Analisis Pengakuan dan Pengukuran Aktiva Tetap Pada PT. Waskita Karya Pusat Jakarta - Shafa Amalia; Syifa Amelia; Melvietha Ocyanie Velenchya; Nur Ayu Oktafiani; Hafiah Salma (BADAN PENERBIT STIEPARI PRESS, 2024)
Fixed assets are factors that greatly support a company’s business success. Fixed assets enable the operational activities of a company to run well and smoothly. The treatment of fixed assets in an entity must be ajusted to the applicable standards, namely the Financial Accounting Standart (PSAK) Number 16, because fixed assets will be recorded in the financial statements. The objective of this research is to know the accounting treatment must be in accordance with PSAK No.16 at PT. Waskita Karya Jakarta so as not mislead its users..The type of research that is done is descriptive research. Based on the results of research conducted, the company set the acquisition price for fixed assets sometimes does not occur uniformity for the acquisition price of fixed assets, the management company has never done or acknowledge the decline and write-off of fixed assets while the method of depreciation is done every year against all types of assets using straight-line depreciation method consistently each year by applying the straight-line method and not deviating from generally accepted accounting standards and any purchase of fixed assets for the operations of the company are recorded at historical cost as the basis for measuring its fixed assets.